About Meat Products - Atajanova Maftuna Zafarovna; Rajapov Otabek Hajiboyevich (Peerian Journals Publishing, 2022)
The article presents the advantages of rabbit meat in contrast to cattle, sheep, goats, horses, camels, Meats, based on the analysis of the work necessary to be carried out on the sustainable development of the meat production sector, increase production volumes, strengthen the feed base.
Keywords: Food safety; cattle meat; mutton; goat meat